Enhancing Madrasah Excellence: Leadership of Principals in Creating Madrasah Research - Rahman, Wahyudin; Salong, Amjad; Setyaningsih, Rina; Pujianti, Etika; Asmarany, Anugriaty Indah (Al-Hayat: Journal of Islamic Education, 2024)
This research aims to describe how program planning, implementation processes and supervision are applied in madrasah. The method used is a qualitative approach, data was collected through observation, interviews and document analysis. Research subjects include principals, quality development teams, supervisors, committees, teachers and supervisors. Data validation uses data triangulation. Data analysis is carried out through data condensation, data presentation and conclusions. The results of this study revealed that programme planning begins at the beginning of the year with a joint meeting between the principal, teaching team and other stakeholders. In the meeting, they discuss the formation of the research class, set the curriculum, and detail the programme plan. The programme is organised by assigning teachers who are competent in the field of research, forming an implementation structure, and a quality development unit. Programme implementation went according to plan, focusing on improving students' knowledge, developing a literacy culture, developing writing skills and participating in competitions. One of the main limitations is that programme supervision still needs to be improved. This may hinder effective monitoring and evaluation of the programme's progress. The study has limitations as it only focuses on one variable madrasah. Therefore, the generalisation of the results of this study to other madrasahs may be limited. This study makes a valuable contribution to understanding madrasah improvement practices in student-conducted research, thus providing essential and relevant insights for improving the quality of education in madrasahs.